The Relationship Of Mom's Knowledge About Nutritional Needs With Weight Increase During Pregnancy At The Clinic Manda In 2019 - Rizky Andriani Bakara Bakara; Desi Anggraini Anggraini (Institute of Computer Science (IOCS), 2019)
A mother who does not have or is malnourished during pregnancy, the baby in her womb will be malnourished. If this continues and is not addressed immediately, the baby will be born with low birth weight. This study aims to determine the relationship between maternal knowledge about nutritional needs and weight gain during pregnancy at the Manda Clinic. The type of research used was analytical observational with a cross-sectional approach and the population in this study were all mothers at the Manda Clinic and the sample of this study was 30 pregnant women at the Manda Clinic in 2019. The results of this study indicate that the majority of the distribution of characteristics of mothers who are aged 23-30 years (56, 7%) the majority of the distribution of characteristics of mothers who have secondary education (SMA) (80%) and the majority of the distribution of characteristics of mothers who have jobs (83.3%), and the majority of the distribution of knowledge of mothers is sufficient (60%). It is recommended for pregnant women to seek more information about nutritional needs during pregnancy.